2003
DOI: 10.1097/01.ta.0000093395.34097.56
|View full text |Cite
|
Sign up to set email alerts
|

Daily Multidisciplinary Rounds Shorten Length of Stay for Trauma Patients

Abstract: By providing a forum for clear communications among all providers, discharge rounds have streamlined the care of complex trauma patients. As health care resources become ever more constrained, this sort of multidisciplinary effort is a viable option for senior physicians to directly impact hospital performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
91
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(98 citation statements)
references
References 24 publications
6
91
0
1
Order By: Relevance
“…50,56 Moreover, first studies on the effects of changes in the design of work systems and processes indicate that restructuring toward a team-based approach improves staff well-being and the quality and safety of patient care. 52,57 Teamwork behaviors related to patient safety Observational studies of teamwork have identified patterns of communication, coordination, and leadership that support effective teamwork. However, only a few studies could establish a direct link between specific teamwork behaviors and clinical performance or patient outcome.…”
Section: Healthcare Providers Perceptions Of Teamwork In Dynamic Medimentioning
confidence: 99%
“…50,56 Moreover, first studies on the effects of changes in the design of work systems and processes indicate that restructuring toward a team-based approach improves staff well-being and the quality and safety of patient care. 52,57 Teamwork behaviors related to patient safety Observational studies of teamwork have identified patterns of communication, coordination, and leadership that support effective teamwork. However, only a few studies could establish a direct link between specific teamwork behaviors and clinical performance or patient outcome.…”
Section: Healthcare Providers Perceptions Of Teamwork In Dynamic Medimentioning
confidence: 99%
“…Participation in trauma team activities was low, presumably due to few dedicated trauma physiotherapists and varied trauma and physiotherapy team service structure. Of particular note is that physiotherapists attended ward rounds at less than 50% of the sites, despite research that shows their participation in this activity can reduce trauma patient hospital length of stay (Dutton et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…4,[8][9][10][11] Measurable outcomes such as shorter length of stay, improved morbidity and mortality, and decreased pulmonary complications (ventilator-associated infections, acute respiratory distress syndrome) have been reported in trauma, orthopedic, cardiac surgery, and critical care programs that utilize a format including care providers across multiple specialties and all points of patient care. 5,[12][13][14] Berkshire Medical Center applied this multidisciplinary approach to the care of all medical inpatients. Initially, the primary focus was to improve process measures such as the American Heart Association's Get With the Guidelines program and CMS core measures related to acute myocardial infarction and community-acquired pneumonia.…”
Section: Discussionmentioning
confidence: 99%